2018
DOI: 10.1002/apj.2183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cobalt as dopant on surface morphologies of undoped ZnO nanostructured thin films

Abstract: This study is aimed to investigate the effect of cobalt, as dopant, on the surface morphologies of nanostructured ZnO thin films. Four different cobalt‐doped ZnO morphologies were prepared by low‐temperature hydrothermal solution deposition, on 2 different substrates—clean glass (CG) and direct‐current magnetron‐sputtered (MS) ZnO glass. An inverse relationship between dopant concentration and grain size was obtained in morphologies obtained from the mixture of solution Zn(NO3)2 + HMT + Co(NO)3.6H2O. No specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Ali et al reported co-doped ZnO and found an inverse relationship between dopant concentration and grain size. 27 The decrease of particle size results from the influence of doping elements on the crystallization and nucleation rate of the material, which hinders the crystallite growth of particles. 27,28 The XRD patterns of the CVO and CVO-s samples are shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ali et al reported co-doped ZnO and found an inverse relationship between dopant concentration and grain size. 27 The decrease of particle size results from the influence of doping elements on the crystallization and nucleation rate of the material, which hinders the crystallite growth of particles. 27,28 The XRD patterns of the CVO and CVO-s samples are shown in Fig.…”
mentioning
confidence: 99%
“…27 The decrease of particle size results from the influence of doping elements on the crystallization and nucleation rate of the material, which hinders the crystallite growth of particles. 27,28…”
mentioning
confidence: 99%